Pengaruh partisipasi anggaran terhadap senjangan anggaran dengan ketidakpastian lingkungan dan komitmen organisasi sebagai variabel moderating pada perbankan swasta di Pekanbaru - Feni Amelia; Yusralaini '; Al-azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The involvement of many stakeholders in the budgeting process has a direct impact on human behavior. Budgetary slack is influenced by several factors including the subordinate participation in the preparation of the budget. Participation in the preparation of the budget will increase the responsibilities and performance of subordinates. Besides participation in the preparation of budgets, budgetary slack can also be caused by the views on the environment and organizational commitment. Environmental uncertainty is the perception of members of the organization in anticipation of the influence of environmental factors on the organization. The population in this study is a private bank operating in Pekanbaru registered in Bank Indonesia in 2012, amounting to 33 banks. Sample collection using nonprobability sampling technique in which the method used was purposive sampling. Each bank sent four questionnaires so that the total amount to 132 questionnaires distributed questionnaires. The data obtained will then be analyzed with multiple linear regression method. The test results indicate that budgetary participation affects the budgetary slack. Then environmental uncertainty moderates the relationship between organizational commitment budgetary participation and budgetary slack.Keywords: Participation Budget, budgetary slack, Environmental Uncertainty and Organizational Commitment.